The effect of loading direction on the dynamic damage in lean duplex stainless steel 2101 - Ameri, A.; Escobedo-Diaz, J.; Quadir, Md Zakaria; Brown, A.; Ashraf, M.; Hazell, P. (2018)
© 2018 Author(s). The effect of loading direction on the spall strength and damage in Lean Duplex Stainless Steel 2101 (LDSS 2101) has been investigated. Experiments were conducted in a single stage gas-gun to test the spall strength of LDSS 2101 along the Rolling Direction (RD), Transverse Direction (TD) and Normal Direction (ND). Microstructural examinations were conducted using optical microscopy and Electron Backscatter Diffraction (EBSD). LDSS 2101 showed similar spall strength in all considered directions. However, the amount of spall damage was dependent on the loading direction. Moreover, most of the spall damage was accommodated within the ferrite phase.